Job creation, job destruction and labour demand in Slovenia - Stefan Bojnec; Jozef Konings (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
This paper uses a unique firm level data base of traditional and newly established private enterprises to investigate gross job flows and labour demand in the transition period in Slovenia. We find that job destruction dominates job creation in the early years of transition, but later in the transition job destruction diminishes. The excess job reallocation rate, a measure for restructuring, is found to be rather low. We find that newly established private firms or de novo firms are fundamentally the most dynamic ones in terms of job creation. We estimate a reduced labour demand equation controlling for ownership and competitive pressure and find that the estimated employment elasticity with respect to sales is rather low, 12%. We do not find any difference in this elasticity if we split the sample in expanding versus contracting firms. Furthermore we cannot find evidence that competitive pressure has any impact on the demand for labour. We do find that de novo firms have a higher employment growth than traditional firms.
Keywords: J63; 330; Job creation; Job destruction; Slovenia; Transition; Private firms